Potensi Bakteri Rizosfer Tanah Salin Sebagai Rizobakteri Pemacu Pertumbuhan Tanaman Ditanah Salin - Kalis Amartani (Jurnal Riset Rumpun Ilmu Tanaman, 2024)
The potential of rhizobacteria as plant growth promoters in increasing crop production in saline soils continues to be carried out by exploring the types of isolates from the rhizosphere of saline soils. The purpose of this study was to obtain the types of isolates that have the potential to be developed as biofertilizers in saline soils. The research was conducted by isolating rhizosphere soil from saline soil and then testing the ability of the resulting isolates to produce phytohormones in the form of IAA, the ability to dissolve phosphate, the ability to fix nitrogen and the ability to produce the enzyme ACC deaminase. The results showed that isolates KNW 2.1, KNW 2.2, KNW 2.3 and KNW 3.2 have potential as rhizobacteria that promote plant growth in saline soils as indicated by their ability to produce the hormone IAA, the ability to dissolve phosphate, the ability to fix nitrogen, and the ability to produce the enzyme ACC deaminase which is higher than the other isolates.